PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR KEBUGARAN JASMANI SISWA KELAS XI IPS I SMA NEGERI 1 BANJARBARU - Rijaldi; Purnama Indah, Eka; Sani, Abdullah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Through the use of a cooperative learning approach akin to STAD (Student Teams Achievement Division), this study attempts to enhance the learning outcomes of students' physical fitness in grade XI IPS 1 SMA Negeri 1 Banjarbaru. The low learning outcomes of students using physical fitness activity materials, such as push-ups, sit-ups, and shuttle runs, as well as their lack of active participation in the learning process, are the driving forces behind this study. Classroom Action Research (PTK) is the sort of study that is employed, and it is conducted in two cycles with phases of planning, action execution, observation, and reflection. Thirty-six students made up the research subjects. Techniques for gathering data include documentation, learning outcome tests, and observation. The study's findings demonstrate that implementing the STAD-style cooperative learning paradigm can enhance student learning outcomes. In the pre-cycle stage, the average score of students was 62.02 or 22% with a low level of completeness. In the first cycle, learning completeness increased to 61% with 22 students achieving completeness. Furthermore, in the second cycle, the average score increased to 84.97 with a completeness rate of 89% or as many as 32 students had completed their studies. In addition to improving learning outcomes, the implementation of the STAD model also increases the activeness, cooperation, motivation, and participation of students in the PJOK learning process.